The Impact of Internet and Technology on E-healthcare Business - Dhage, Seemit (2007)
The Healthcare Business is made up of three players, the patient group, the medical profession and the health care business i.e. Pharmaceuticals or Medical equipment industry. Healthcare Business and its elements have been slow to adapt to changes taking place in technology. The lag could be attributed partly to the traditional methods of doing business in this sector, and partly could be attributed to the lack of co-ordination and knowledge sharing between the three players. The linkage between the three players is interesting to understand. The changes brought about by one player directly have an impact on the other two elements. For example, if patients use the internet to learn and obtain information about a disease, it might affect the Doctor-Patient relationship, as the Doctor might feel threatened and challenged by the informed patient. Also if the patients use internet more often, the pharmaceutical industry will soon have to focus on online retailing of medicines.